Exploring the Economic Potential of Local Seafood Processing Industries in Bulukumba - Prabandari, Widati Layoga; Hamzah, Haerunnisa; Angriani, Marshanda (Scieclouds Publishing, 2023)
This paper aims at establishing the economic prospects of the local seafood processing industries in Bulukumba, South Sulawesi by analyzing the prospect, constraints and consideration on the development of fisheries’ sector. It should be noted that the region is endowed with rich sea resources that hold high prospects for the development of the seaborne economy though the processing of seafood. But the research finds out factors that slows development such as absence of infrastructures, lack of enough human capital, and others which inhibit development of sustainable production systems. The research also reveals potential benefits as the global market demand for seafood from sustainable sources rises and potential employment opportunities are seen especially for women and the youth in rural regions. Based on the results identified herein, subsequent investments in the above-mentioned areas would be important for unlocking the economy of the seafood processing industry in Bulukumba. The study shall prove useful to policymakers and stakeholders with an interest in the enhancement of competitiveness of small-scale shellfish operation in developing countries to help contribute towards economic growth and sustenance of the region.